Marine protected area : a case study in north-easter Iloilo, Philippines : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Economics, Massey University, Palmerston North, New Zealand - Fernandez, Cheryl Joy Jardiolin (Massey University, 2010)
Marine Protected Area (MPA), as a fisheries management tool has been promoted by both national and local conservationists and has provided de facto illustrations of integrated coastal management (ICM) in the Philippines. However, conflict is inevitable in the implementation of public policy such as the MPA because of contrasting objectives and expectations from various stakeholders. Coupled with non-human (e.g. MPA size) and human (e.g. mismanagement) threats, conflict becomes a hindrance to MPA effectivity. In the Philippines alone, only 10-20% of the 500 MPAs are attaining their objectives. This study presents an overview of MPA management and examines the interaction between the civil society and market forces of institutional arrangements in the case of North-Eastern Iloilo (NI) in the Philippines. It discusses overall scenarios that resemble conflict between various national, local and international sectors, assessing MPA success factors and the expected implications from such implementation. Results from key informant, focus-group discussion and social survey show that there are problems on MPA management in the region. Using data and strategic analyses, it presents that minimisation of conflicts amongst actors should be the primary goal of the NI municipalities. In addition, MPA size and membership to organisations are also significant factors of success. Moreover, the analysis from a simple correlation to complex Principal Component Analysis (PCA) and Canonical Correlation Analysis (CCA) conclude that information on MPA regulation does not directly contribute to the improvement in MPA management. It implies that a focus on informing stakeholders about the benefits of having an MPA and its regulations is ineffective. The focus should be on the reduction of conflict between economic actors - for free riding problems are currently occurring, thus minimising conflict by conflict resolution and proper incentives. However, there are still remaining challenges on MPA management, for not all factors are incorporated on this study. The challenge now is on how to identify the remaining factors and integrate them into policies and implementations to improve the overall condition of coastal communities.
Keywords: Coastal management; Fisheries management; Fields of Research::340000 Economics::340200 Applied Economics::340202 Environment and resource economics